Comparison of Endophthalmitis Rates after Alcohol-Based Chlorhexidine and Povidone-Iodine Antisepsis for Intravitreal Injections - Mishra, Amit V; Tong, C Maya; Faes, Livia; Cheema, Marvi K; Plemel, David; Rubin, Uriel; Bao, Bo; Nazarali, Samir; Lapere, Steven R J; Somani, Rizwan; Hinz, Brad J; Tennant, Matthew T S (Ophthalmology retina, 2024)
Intravitreal injections (IVIs) are the most frequently performed intraocular procedure in Canada. Povidone-iodine (PI) is the current gold standard for antisepsis for IVI and is widely used; chlorhexidine (CH) is a possible alternative antiseptic agent. This study aims to compare rates of endophthalmitis after IVI with 0.05% chlorhexidine with a 4% alcohol base antisepsis to rates of endophthalmitis after IVI with 10% PI antisepsis. Retrospective cohort study. Eyes that received IVI between May 2019 and October 2022 at a group retina practice in Edmonton, Canada. Eyes at a single center received focal conjunctival application of either 10% PI antisepsis or 0.05% CH in 4% alcohol antisepsis for 30 seconds before each IVI. Rates of endophthalmitis between the PI and CH groups. A total of 170 952 IVIs were performed during the study period. A total of 31 135 were performed using CH prophylaxis compared with 139 817 with PI prophylaxis. Among all IVIs there were 49 total cases of endophthalmitis, 29 in the PI group (0.021%) and 20 in the CH group (0.064%). There was a statistically significant difference in the rates of endophthalmitis between the 2 groups (P < 0.001). The odds ratio for developing endophthalmitis with CH antisepsis was 3.1 (95% confidence interval, 1.9-5.2) compared with PI antisepsis. There were increased odds of developing endophthalmitis with aflibercept injection compared with bevacizumab (odds ratio, 3.48; 95% confidence interval, 2.09-7.24). There is a statistically significant difference in rates of endophthalmitis between alcohol-based CH and PI antisepsis for IVI in our patient population utilizing the methods discussed. In our center, alcohol-based CH is now considered a second-line antiseptic agent. Further studies are warranted to further assess the endophthalmitis rate utilizing these 2 antiseptic agents. Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.